Research on the Characteristics and Mechanism of the Cumulative Release of Antimony from an Antimony Smelting Slag Stacking Area under Rainfall Leaching - Bozhi Ren; Yingying Zhou; Andrew S. Hursthouse; Renjian Deng (Journal of Analytical Methods in Chemistry)
We aimed to study the characteristics and the mechanism of the cumulative release of antimony at an antimony smelting slag stacking area in southern China. A series of dynamic and static leaching experiments to simulate the effects of rainfall were carried out. The results showed that the release of antimony from smelting slag increased with a decrease in the solid-liquid ratio, and the maximum accumulated release was found to be 42.13 mg Sb/kg waste and 34.26 mg Sb/kg waste with a solid/liquid ratio of 1 : 20; the maximum amount of antimony was released within 149–420 μm size fraction with 7.09 mg/L of the cumulative leaching. Also, the antimony release was the greatest and most rapid at pH 7.0 with the minimum release found at pH 4.0. With an increase in rainfall duration, the antimony release increased. The influence of variation in rainfall intensity on the release of antimony from smelting slag was small.